2005
DOI: 10.1111/j.1467-9620.2005.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

What Makes the Difference? A Practical Analysis of Research on the Effectiveness of Distance Education

Abstract: This article reports findings of a meta-analytical study of research on distance education. The purpose of this study was to identify factors that affect the effectiveness of distance education. The results show that although the aggregated data of available studies show no significant difference in outcomes between distance education and face-to-face education as previous research reviews suggest, there is remarkable difference across the studies. Further examination of the difference reveals that distance ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
255
0
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(278 citation statements)
references
References 49 publications
8
255
0
15
Order By: Relevance
“…A meta-analysis research by Zhao, et al (2005) found that the instructor's involvement was the most significant factor in interactions between the teacher and students. However, the present research indicates that student-content interaction makes the highest contribution to the e-learning interactions.…”
Section: E-learning Interactions and Students' Academic Achievementmentioning
confidence: 99%
“…A meta-analysis research by Zhao, et al (2005) found that the instructor's involvement was the most significant factor in interactions between the teacher and students. However, the present research indicates that student-content interaction makes the highest contribution to the e-learning interactions.…”
Section: E-learning Interactions and Students' Academic Achievementmentioning
confidence: 99%
“…The authors also discovered that the distance-learning situations inclined to have further encouraging results when computer-mediated interactions were available. Advantages of mixed learning (a combination of some features of face-to-face and online learning) over completely online learning were discovered by Zhao et al (2005). It was discovered by Zhao et al that the involvement of teacher plays the role of a powerful arbitrating variable.…”
Section: Medium Of Deliverymentioning
confidence: 99%
“…Among these, the foremost concerns are student experience and the quality of online education (Zhao, Lei, Yan, Lai, & Tan, 2005). In an online educational context, instructors tend to monitor student learning less, due to the lack of in-class interactions and no face-to-face meetings.…”
Section: Experience and Learning In Distance Educationmentioning
confidence: 99%
“…Meta-analysis has become an effective way to synthesize the findings on learning outcomes of distance education. Zhao et al (2005) conducted a meta-analysis investigating the effectiveness of distance education. They reviewed 8,840…”
Section: Experience and Learning In Distance Educationmentioning
confidence: 99%